Overweight Adolescents’ Self-Perceived Weight and Weight Control Behaviour: HBSC Study in Finland 1994–2010 - Kristiina Ojala; Jorma Tynjälä; Raili Välimaa; Jari Villberg; Lasse Kannas (Journal of Obesity)
Introduction. Overweight and perception of being overweight, may lead adolescent to lose weight. The aim of the present study was to investigate overweight adolescents’ self-perceived weight, body dissatisfaction, and weight control behaviour during 1994–2010 in Finland. Methods. The country-representative, cross-sectional data of 15-year olds were obtained from the Health Behaviour in School-aged Children (HBSC) study, conducted in 1994 (𝑁=1194; males: 48%), 1998 (𝑁=1545; 49%), 2002 (𝑁=1745; 50%), 2006 (𝑁=1670; 47%), and 2010 (𝑁=2082; 48%). Results. The majority of overweight boys (62–69%) and girls (89–100%) assessed themselves as too fat, and their body image was lower than in nonoverweight adolescents. The highest prevalence of current weight controlling was found in 2006 in males (18%) and in 2010 in females (39%). Conclusion. The phenomena were current and gender differences notable, but there was no statistically significant difference in overweight adolescents’ self-perceived weight, body dissatisfaction, or weight control behaviour between survey years.